The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/cddis.2014.563
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of selenite (Se4+) on arsenite (As3+)-induced apoptosis and differentiation in acute promyelocytic leukemia cells

Abstract: To enhance the therapeutic effects and decrease the adverse effects of arsenic on the treatment of acute promyelocytic leukemia, we investigated the co-effects of selenite (Se4+) and arsenite (As3+) on the apoptosis and differentiation of NB4 cells and primary APL cells. A 1.0-μM concentration of Se4+ prevented the cells from undergoing As3+-induced apoptosis by inhibiting As3+ uptake, eliminating As3+-generated reactive oxygen species, and repressing the mitochondria-mediated intrinsic apoptosis pathway. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 39 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…While we have been pursuing our work, a parallel study has reported abrogation of PML/RARα protein expression following selenite treatment [33]. Consistent with this study, we also provide evidence for abrogation of PML/RARα expression by selenite alone in a different experimental set up.…”
Section: Discussionsupporting
confidence: 86%
“…While we have been pursuing our work, a parallel study has reported abrogation of PML/RARα protein expression following selenite treatment [33]. Consistent with this study, we also provide evidence for abrogation of PML/RARα expression by selenite alone in a different experimental set up.…”
Section: Discussionsupporting
confidence: 86%
“…After 72 h of treatment, 1.6 μM BKM120 increased the percentage of DCF-positive cells, indicating an increase of cellular ROS (Fig. 2 B) 37 . Compared with control, the effect of 9.6 μM olaparib on the accumulation of cellular ROS was not obvious.…”
Section: Resultsmentioning
confidence: 89%
“…N-acetyl-L-cysteine, L-ascorbic acid, and selenite (SeO 3 2− ) prevented AsO 2 − -induced apoptosis, oxidative stress, a cell viability decrease, mitochondrial disfunction, cytochrome c release, and an ROS production increase in experiments with L02 hepatocytes, mouse oligodendrocyte precursor cells, human myeloid leukemia U937 cells, and acute promyelocytic leukemia NB4 cells [279,[299][300][301]. The effect of SeO 3 2− can be caused by the inhibition of AsO 2 − transport in NB4 cells [301]. Pterostilbene or tert-butylhydroquinone activating the Nrf2 pathway alleviated similar AsO 2 − -induced effects in human HaCaT keratinocytes, mouse epidermal JB6 cells, and human epithelial HaCaT cells [302,303].…”
Section: Al(iii) Ga(iii) and In(iiimentioning
confidence: 99%